Raising disabled heroes in sport: challenges and prospects - Abd Rahim, Badruel Hairiel; Mohamad Diah, Nurazzura (Zes Rokman Resources, 2018)
Since 1960s, the involvement of people with disabilities in sport has increased significantly. However, their participation in sports is considered tough compared to their able-bodied peers. Previous studies indicated that limited access to facilities and lack of opportunities were among the challenges faced by this group. Hence, the researchers feel obligated to continuously gain/increase current knowledge especially in the area of sports and disabilities. The objective of this study is to focus on the experiences of student-athletes with disabilities in sport. In order to obtain relevant data, the researchers have recruited ten Malay and Indian goalball student-athletes with vision impairment from Setapak, Kuala Lumpur using the purposive sampling. They are between 14-19 years old and have represented their schools in various competitions. They won several medals at the state and national level tournaments. All data has been transcribed and analysed using thematic approach. The study revealed three main challenges faced by the student-athletes: i) pride in exclusivity, ii) maintaining their interest in sport after completing school and iii) creating public awareness about their involvement in sport. This study proposed for a better outlook on sport and people with disability in Malaysia.